Exempla 2 : arte italiana nella vicenda europea 1960-2000 - Corà, Bruno; Di Felice, Paola; Panzera, Mauro; Sperandio, Angelo; Comune di Teramo (Prato : Gli Ori, 2002)
Agnetti, Vincenzo ; Alfano, Carlo ; Angeli, Franco ; Anselmo, Giovanni ; Bagnoli, Marco ; Bassiri, Bizhan ; Boetti, Alighiero ; Calzolari, Pierpaolo ; Chiari, Giuseppe ; Clemente, Francesco ; Cucchi, Enzo ; de Dominicis, Gino ; Esposito, Diego ; Fabro, Luciano ; Fortuna, Pietro ; Gastini, Marco ; Gilardi, Piero ; Icaro, Paolo ; Kounellis, Jannis ; Mattiacci, Eliseo ; Melani, Fernando ; Merz, Mario ; Merz, Marisa ; Messina, Vittorio ; Mochetti, Maurizio ; Moreni, Mattia ; Nagasawa, Hidetoshi ; Nunzio ; Nuvolo ; Ontani, Luigi ; Paladino, Mimmo ; Paolini, Giulio ; Parmiggiani, Claudio ; Pascali, Pino ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Ranaldi, Renato ; Salvadori, Remo ; Salvo ; Schifano, Mario ; Spagnulo, Giuseppe ; Spalletti, Ettore ; Tirelli, Marco ; Zorio, Gilberto
Italiaans
Exempla 2 : arte italiana nella vicenda europea 1960-2000, Pinacoteca Civica e siti urbani, Comune di Teramo, 19 maggio - 24 novembre 2002
kunstcatalogus
Keywords: Italië